Permanent health education for managers as a tool to combat institutional racism in a Northeastern Brazilian municipality - Matheus Guirra Martins Ferreira; Gilmar Mercês de Jesus; Etna Kaliane Pereira da Silva; Victor Bertino Silva; Mariana Costa da Silva (Salud Colectiva)
This article discusses the experience of a permanent health education initiative focused on institutional racism with health professionals from the Brazilian Unified Health System (SUS) holding management positions in a municipality in the interior of Bahia, in Northeastern Brazil. A workshop was held in September 2022, based on a problematizing methodology called the Maguerez Arc, conducted by residents of the Multiprofessional Family Health Program. Ten managers participated in the workshop, most of whom were women. Despite acknowledging the presence and impact of racism in health services, managers find it challenging to recognize and address racism in its institutional dimension. A recurring discourse aligned with the myth of racial democracy was notable, and a higher level of commitment among Black women was observed throughout the workshop. Permanent health education emerges as an essential strategy to combat racism, necessary to expand such discussions within health services.